Sexually Transmitted Infections Clinics as Strategic Venues for Targeting High Risk Populations for HIV Research and Sexual Health Interventions - Clatts, Michael Craig; Rodríguez-Díaz, Carlos E.; García, Hermes; Vargas-Molina, Ricardo L.; Colón-López, Vivian; Pérez-Rios, Naydi; Goldsmat, Lloyd; Jovet-Toledo, Gerardo G. (Puerto Rico Health Sciences Journal, 2011)
Puerto Rico has one of the highest incidence rates of HIV in the U.S. Concurrent with increases in sexually transmitted infections (STI), an increasing share of the new infections in PR are associated with sexual transmission. Much of the available research on sexual risk in PR derives from STI/HIV surveillance data. There is limited social and epidemiological research on sexual risk in PR, particularly in hidden and often hard-to-reach populations at high risk. Despite the absence of substantial resources that most epidemiological studies require, a research collaboration was initiated in 2007 between researchers in the School of Public Health at the University of Puerto Rico and the Centro Latinoamericano de Enfermedades de Transmisión Sexual (CLETS), one of the largest publicly funded centers for STI /HIV screening and treatment in the San Juan metropolitan area. Structured as a case study in the development of community-based research collaborations, this paper describes the early history and development of the project, including formative research, recruitment and training of students, and evolution in the study design that contributed to the current configuration of the ongoing “Core” study. Preliminary data are presented, highlighting data from a number of subpopulations that may contribute to our understanding of the role of behavioral risk in the STI/HIV epidemics in PR. More generally, the paper may guide the development of similar collaboration elsewhere in the Caribbean where HIV risk is increasing but where resources for research in high risk settings and groups are scarce.